Poverty and Health Monitoring Report - Suzuki, Emi; Sharan, Mona; Bos, Eduard (World Bank, Washington, DC, 2013)
Health data at the national level do not reveal the inequalities associated with poverty within a country; therefore national progress toward health goals can be made without much improvement in the health status of the poor. Poverty quintile analysis is useful here: it disaggregates data on health indicators by the socioeconomic status of households. In this report it is used to study the levels and trends in health inequalities in developing countries. Narrower gaps were evident between the rich and poor on knowledge-related indicators than on practice-related ones. Preventive interventions such as immunization were more equitable across quintiles, while there were more inequities in curative care. Reproductive health indicators showed some of the largest gaps between the rich and poor. Geographically, some regions such as Europe and Central Asia had more equitable health indicators, while others such as South Asia and Sub-Saharan Africa reported larger gaps between the rich and poor. The current levels of progress are insufficient for adequately reducing inequalities, and the poor are at risk of being left behind unless countries take the necessary steps to expand health care to socioeconomically disadvantaged groups.